Design of Isak-Based Financial Report Preparation System for the Jami' Miftahussalam Mosque 35 - Muhammad Angga Permana; Herman Karamoy; Christian Datu (Formosa Journal of Applied Sciences, 2023)
The majority of Indonesian people embrace Islam and mosques are a place of worship, based on ISAK 35 which states that mosques are a form of non-profit organization that must and must make financial reports. Apart from that, a good accounting information system will support internal control regarding cash use. The aim of this research is to analyze the need for an ISAK 35-based financial reporting system to evaluate internal cash control. The type of research used is qualitative research with a descriptive approach. The research results showed that the Jami Miftahussalam Mosque had not prepared financial reports based on applicable standards, the accounting information system was still manual, resulting in weak internal controls. The research was conducted from March 1 to June 10. Furthermore, it is hoped that the mosque will implement the system that has been designed.